Pengaruh Strategi Pembelajaran Aktif Tipe The Great Wind Blows terhadap Tingkat Kecemasan Matematis Siswa di Sekolah Dasar - Setiawan, Herdi; Nurhizrah Gistituati; Azwar Ananda; Rusdinal; Rahmi Putri (Study program PGSD FKIP Universitas Bung Hatta, 2023)
Math anxiety is one of the most serious obstacles in education. Based on the results of observations, there are early indications that students experience anxiety in learning mathematics. The purpose of this study was to see the effect of the great wind blows type of active learning strategy on the level of students' mathematical anxiety. The method used for this paper is a quantitative method using a pre-experimental design. the pre-experimental design with the one group pretest post test design was used because the researcher wanted to see the difference between the level of anxiety before the action was taken and after the action was carried out so that from these results it could be seen whether there was an influence or not from the learning strategy used. The results of this study indicate that the average value of the posttest results obtained an average value of 45.32 with a standard deviation of 8.55 while the pretest results obtained an average value of 54.64 with a standard deviation of 9.21. the great wind blows type of active learning strategy (posttest) tends to decrease compared to before using the great wind blows type of active learning strategy (pretest).